Automation in modern manufacturing: evolution and challenges ("Journal "U". Economy. Management. Finance.", 2025)
The article traces the development of automation in industry: from the mechanization of the 18th–19th centuries to the intelligent systems of Industry 4.0. Key technological stages are described, along with their contribution to increasing productivity and product quality. The main challenges are examined: technological unemployment, high implementation costs, cyber risks, and the need for workforce retraining.
Keywords: automation; Industry 4.0; technological unemployment; retraining